Pastoral Rangelands in Sub-Saharan Africa : Strategies for Sustainable Development - Lusigi, W. J.; Buursink, John (World Bank, Washington, DC, 2012)
The Sahel Operational Review (SOR) seeks to accelerate the transfer of lessons learned in natural resource management from ongoing Bank projects to the design of new Bank projects. This paper is the final report of the second phase of the SOR. It summarizes 29 SOR activities between 1989 and July 1994, including project reviews, seminars, workshops, conferences, and studies. This final report is an attempt to incorporate the major lessons and findings from these activities into one publication, as well as to guide task managers through the various books and papers produced by the SOR program.